THE ROLE OF PRODUCT INNOVATION IN MEDIATING THE INFLUENCE OF SOCIAL MEDIA MARKETING ON BUSINESS PERFORMANCE (Study of Silver Crafts MSMEs in Celuk Village) - Kadek Karina Weda Cita; Ni Made Asti Aksari (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
The economy in Indonesia continues to experience growth along with advances in information technology and globalization resulting in high competitiveness in various industrial sectors. Large-scale industries and MSMEs are affected by the effects of globalization. One of the MSME sectors that is currently continuing to develop is the crafts sector. The creative economy's most labor-intensive sector, the craft sector helps to boost the earnings of those involved in the creative business. The reason of this observation is to examine how innovation for product influences social media marketing's impact on Silver Craft MSMEs' business performance in Celuk Village. This study was was conducted at the Silver Craft MSMEs in Celuk Village, with 117 MSMEs selected using a saturated sampling approach. Data have been accumulated using a method by survey through questionnaire given immediately. The data gathered was subsequently evaluated using path analysis methods. The research results shown that marketing in social media has a good impact in significantly on business performance, social media marketing has a positive and impact in significantly on innovation for product, innovation for product has a good and impact in significantly on business performance, and marketing in social media has an indirect effect on business performance through innovation for product.